POTENSI SPIRITUALITAS GURU PAI DI GARUT SELATAN - Daris Tamin (Jurnal Pendidikan Agama Islam, 2015)
This study aimed to get an overview of the religious spirituality potential of Islamic Studies teacher in South Garut region, West Java Province. This research used survey method with questionnaires as the instrument for collecting primary data. Respondents in this research amounted to 130 Islamic Studies teachers in South Garut region, West Java Province. Based on result of this research, found that the description of religious spirituality potential of Islamic Studies teachers SouthGarut, West Java Provinceis generallyconsidered good. As for the details, as follows: (1) the belief dimensions in the excellent category, (2) the worship dimensions in good category, (3) the intellection dimensions in good category, (4) the moral dimensions in good categories. And (5) the physical dimension in good categories.